1981
DOI: 10.1620/tjem.135.215
|View full text |Cite
|
Sign up to set email alerts
|

Probable superoxide therapy of experimental cancer with d-penicillamine.

Abstract: A sublethal dose of D-penicillamine (DP) induced hyperlipoperoxidemia and hypocupremia in old rats. Treatment of cancer cells in vitro and in vivo with DP resulted in appreciable suppression of cell multiplication and a remarkable inhibition of tumor growth. Erythropoiesis did not seem to be affected by DP. The selective effect of DP seems to have resulted from the reduced superoxide dismutase activity and/or defective Mn superoxide dismutase. ----superoxide therapy; experimental cancer; D-penicillamine In mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…On account of the biological differences, the protein synthesis of eukaryotic cells may not be directly affected by doxycycline (Alberts et al 1983). Therefore, the anti-cancer effects may first be arising from cell kill through chelation of heavy metals and resultant inactivation of relevant vital enzymes such as superoxide dismutase (Okuyama and Mishina 1981) and DNA polymerase (Slater et al 1971), and through deprivation of HDL-cholesterol from the cell membranes, presumably resulting in disintegration of cancer cells (Bierman and Glomset 1981). They may secondly be related to the tendency to revert along the line of evolution of neoplastic cells 1985a, b, 1986Selata 1984).…”
Section: Resultsmentioning
confidence: 99%
“…On account of the biological differences, the protein synthesis of eukaryotic cells may not be directly affected by doxycycline (Alberts et al 1983). Therefore, the anti-cancer effects may first be arising from cell kill through chelation of heavy metals and resultant inactivation of relevant vital enzymes such as superoxide dismutase (Okuyama and Mishina 1981) and DNA polymerase (Slater et al 1971), and through deprivation of HDL-cholesterol from the cell membranes, presumably resulting in disintegration of cancer cells (Bierman and Glomset 1981). They may secondly be related to the tendency to revert along the line of evolution of neoplastic cells 1985a, b, 1986Selata 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of studies above, it was concluded that PGA− d -pen was able to successfully deliver d -pen to cancer cells. Although high doses of the conjugate ( d -pen equivalent) are required to achieve beneficial effect if used alone, it has been reported that tumorigenic cells are 30- to 100-fold more sensitive to treatment with d -pen compared to normal cells. , This in-built selectivity makes d -pen a potential agent for development as an anticancer drug. However, it may be essential to combine it with a standard chemotherapy regimen when used in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Although high doses of the conjugate (D-pen equivalent) are required to achieve beneficial effect if used alone, it has been reported that tumorigenic cells are 30-to 100-fold more sensitive to treatment with D-pen compared to normal cells. 42,47 This in-built selectivity makes D-pen a potential agent for development as an anticancer drug.…”
Section: Discussionmentioning
confidence: 99%
“…The scheme does not include the reported effects on activation of angiostatin by SH groups of DPA [34], which may explain the angiosuppressive properties of DPA. Okuyama and Mishina [23] suggest that DPA inhibits the activity of superoxide dismutase, thus increasing the peroxidative damage to cells.…”
Section: Chelates Cu Znmentioning
confidence: 99%
“…1). after systematic administration in the diet or parenteral injection [18][19][20][21][22][23][24]. The high water solubility of these drugs and their fast metabolism temper their efficacy due to the fast synthesis of LOX.…”
Section: Introductionmentioning
confidence: 99%